Enhancing Students’ Learning Motivation through Wordwall Educational Games in Mathematics - Febrianti, Ika; Baidullah, Baidullah (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Learning motivation is a crucial component that determines students’ academic success, particularly in subjects such as mathematics, which are often perceived as difficult and less appealing. The low level of students’ motivation in mathematics is one of the key factors contributing to the insufficient attainment of basic competencies at the elementary school level. Therefore, innovative approaches are needed to effectively enhance student engagement and enthusiasm for learning. This study aims to analyze the effect of using Wordwall-based educational games on elementary school students’ motivation in learning mathematics. A quantitative approach was employed with a one-group pretest–posttest design. The research subjects were 30 fourth-grade students at SD Negeri 2 Jeumpa, selected through a total sampling technique. The data collection instrument was a validated learning motivation questionnaire with high reliability. Data were obtained through measurements conducted before and after the implementation of learning using Wordwall. The results of the analysis, using a paired sample t-test, revealed a significant increase in students’ learning motivation (p < 0.05), with the mean posttest score being higher than the pretest score. Most students who were initially categorized at a moderate level showed improvement to high and very high categories after the treatment. These findings indicate that the use of Wordwall contributes positively to enhancing students’ learning motivation in mathematics. This study provides novel evidence of the potential of game-based learning platforms, particularly Wordwall, in fostering motivation in mathematics learning, an area that remains underexplored in the Indonesian elementary school context. The study recommends the integration of Wordwall as an innovative strategy to increase student engagement, with further development focusing on cognitive aspects and learning outcomes.